(3JQJjH GdaJGhi GdRjfjIs - (3eMeO Hf YHO Gddg Hf CMeO, GdNWjH GdYeQj GdJeQJGTj GdZRj GdMfaj, TeS GdOjf , (B1004 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; MeOG def CHQR GdYGde hHYO ajbhd eMeO Hf YHO Gddg Hf CMeO GdNWjH deG cGf cJGH GdaJGhi GdefShHI Edi Rjf Hf fLjH GdeUQj cJGHG eTJedG Ydi HYV GLhHg jMJGL EdjgG efgG dYOe JQJjHgG CQOJ Cf CQJHgGs
(3BNQgG (B:s
(3hJYGhf Ydjg Yfg Cf jCNPg efg HGdGeUGOQI jVef GdKGfj aj gPg GdUhQI eG CNPg GdXGde gPG gh GdeaJi Hg GdeJCNQhf ef YdeGFfGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 239s
(3eYLe GdeDdajf (B3 / 427s
(3gOjI GdYGQajf (B2 / 262s
(3NdGUI GdCKQ (B4 / 18s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs